A Simple Modelling System to Forecast Tropospheric ozone concentrations - Beneito, Jordi; Soler, Maria Rosa; Alarcón, Marta (Física de la Tierra, 2008)
This study reports the development of a simple, operational modelling system to forecast surface ozone concentrations. The model consists of 3 modules corresponding to meteorological, emission and photochemical models linked by a program written in Visual Fortran. The system was applied during later spring-summer 2003 and 2004 in different areas of Catalonia, in north-east Spain. Accuracy in predicting maximum daily ozone concentration was between 15 and 20 μgm-3, while there was a tendency to overestimate, which ranged from 0.5 to 7 μgm-3.We also tested the model’s ability to forecast concentrations within different levels concentrations, especially those are higher than 180 μgm-3, which could be of practical use to air-quality managers. Between 65% and 90% of the forecasts were correct, depending on the area forecasted. The system was also used to make a sensitivity analysis for all areas of the simulation. This study helps to find strategies for reducing ozone levels because it provides information about how the ozone concentration responds to changes in the emissions of its precursors.